1999
DOI: 10.1046/j.1469-0705.1999.14030183.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome: it is always bilateral?

Abstract: Polycystic ovary syndrome does not predetermine a single ultrasonographic and Doppler pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In 1999, in an observational study of 16 women with unilateral PCO and 20 women with bilateral PCO, Battaglia and co-workers [42] reported that the women in the latter group had higher concentrations of androstenedione and LH to FSH ratios. Furthermore, in women with unilateral PCO, grey scale and Doppler ultrasound showed different features in the affected and the unaffected ovary, similar to the appearance of the polycystic and the normal ovary, respectively [42]. …”
Section: The Unilateral Polycystic Ovarymentioning
confidence: 99%
“…In 1999, in an observational study of 16 women with unilateral PCO and 20 women with bilateral PCO, Battaglia and co-workers [42] reported that the women in the latter group had higher concentrations of androstenedione and LH to FSH ratios. Furthermore, in women with unilateral PCO, grey scale and Doppler ultrasound showed different features in the affected and the unaffected ovary, similar to the appearance of the polycystic and the normal ovary, respectively [42]. …”
Section: The Unilateral Polycystic Ovarymentioning
confidence: 99%
“…No difference was seen in LH, FSH, estradiol, or testosterone levels 14 not only were serum LH and testosterone significantly higher in the bilateral group but LH as well as insulin levels in follicular fluid were also significantly higher in women with bilateral polycystic ovaries. In an observational study in adults, Battaglia et al found that women with bilateral PCOS had significantly higher androstenedione and LH/FSH ratio than matched women with unilateral PCOS.…”
Section: Discussionmentioning
confidence: 67%
“…3). The authors speculated that in unilateral or in partial PCOS the peripheral expression of ovarian receptors for LH or environmental factors (surgery, infections, ovarian vascularization) may limit the morphological and functional features of PCOS to a single ovary or to a specific portion of the ovaries [61,62].…”
Section: Identification Of Polycystic Ovaries On Pelvic Ultrasoundmentioning
confidence: 99%